Emergency Medical Services Naloxone Access: A National Systematic Legal Review. (October 2014) - Davis, Corey S.; Southwell, Jessica K.; Niehaus, Virginia Radford; Walley, Alexander Y.; Dailey, Michael W.; Gaddis, Gary M.
Abstract Objectives Fatal opioid overdose in the United States is at epidemic levels. Naloxone, an effective opioid antidote, is commonly administered by advanced emergency medical services (EMS) personnel in the prehospital setting. While states are rapidly moving to increase access to naloxone for community bystanders, the EMS system remains the primary source for out‐of‐hospital naloxone access. Many communities have limited advanced EMS response capability and therefore may not have prehospital access to the medication indicated for opioid overdose reversal. The goal of this research was to determine the authority of different levels of EMS personnel to administer naloxone for the reversal of opioid overdose in the United States, Guam, and Puerto Rico. Methods The authors systematically reviewed the scope of practice of EMS personnel regarding administration of naloxone for the reversal of opioid overdose. All relevant laws, regulations, and policies from the 50 U. S. states, the District of Columbia, Guam, and Puerto Rico in effect in November 2013 were identified, reviewed, and coded to determine the authority of EMS personnel at four levels (in increasing order of training: emergency medical responders [EMRs], emergency medical technicians [EMTs], intermediate/advanced EMTs, and paramedics) to administer naloxone. Where available, protocols governing route and dose of administration were also identified and analyzed. Results All 53 jurisdictions license or certify EMS personnel at the paramedic level, and all permit paramedics to administer naloxone. Of the 48 jurisdictions with intermediate‐level EMS personnel, all but one authorized those personnel to administer naloxone as of November 2013. Twelve jurisdictions explicitly permitted EMTs and two permitted EMRs to administer naloxone. At least five jurisdictions modified law or policy to expand EMT access to naloxone in 2013. There is wide variation between states regarding EMS naloxone dosing protocol and route of administration. Conclusions Naloxone administration is standard for paramedic and intermediate‐level EMS personnel, but most states do not allow basic life support (BLS) personnel to administer this medication. Standards consistent with available medical evidence for naloxone administration, dosing, and route of administration should be implemented at each EMS level of certification.